Analisis Pengaruh Kemampuan Dinamis Organisasi terhadap Segmentasi, Targeting, dan Positioning - Santoso, Niki Agus; Rinova, Dora (Business Perspective Journal, 2024)
An organization's ability to be dynamic amidst global competition is very much needed, in order to be able to adapt quickly to market changes and continuously developing business trends. Organizations that are unable to adapt quickly will be left behind and find it difficult to compete with their competitors. This lag makes organizations compete to change and adapt to the business environment around them. An appropriate marketing concept is also very important to help organizations compete in the global market, one of which is by implementing segmentation, targeting and positioning (STP). This research aims to determine the influence of an organization's Dynamic Capabilities on Segmentation, Targeting & Positioning. So that an organization can maximize its ability to survive in conditions of global competition. This research is supported by the AIDA Models, Nayaka and SECI models, in addition to literature studies from scientific journals describing the factors that influence the research. The research results show that in carrying out STP, organizations need to have adequate dynamic capabilities to create competitive advantages and maintain their position in the market. This helps the organization in maintaining its position in the market by improving the quality of products or services and creating added value for consumers. Organizations that have good dynamic capabilities will be able to optimize their resources to create higher quality products or services and create added value for consumers. This will help the organization in improving its position in the market and winning the competition. In implication, organizations need dynamic capabilities in innovation, adaptation, organizational collaboration, and decision making to create greater opportunities. Keywords: Dynamic Capabilities; Segmentation, Targeting, Positioning